The Difference of Antibacterial Power between Cocoa Peel (Theobroma Cacao L.) Extract 6% compared to Chlorhexidine Digluconate 2% Againts Streptococcus mutans (In vitro) - Alissa Amanda; Tamara Yuanita; Galih Sampoerno (Conservative Dentistry Journal, 2021)
Background: Before restoration, it is necessary to clean the cavity from the smear layer and residual bacteria such as Sreptococcus mutans using a 'gold standard' cavity cleanser, namely 2% Chlorhexidine digluconate (CHX), however CHX 2% has a disadvantage of having a toxic effect on fibroblasts, osteoblasts, myoblasts, odontoblast-like cells, Chinese hamster ovary cells, and buccal epithelial cells. The shortcomings of the 2% CHX triggered researchers to look for alternative cavity cleansers that are more biocompatible, namely cocoa peel extract because it contains of antibacterial compounds including alkaloids, flavonoids, tannins, saponins, and terponoids with a non-toxic 6% concentration. Purpose: To analyze the difference of antibacterial activity between cocoa peel extract with a concentration of 6% compared to chlorhexidine digluconate 2% against Streptococcus mutans. Methods: This research was an in vitro laboratory experimental study with the posttest only control group design which included two treatment groups, namely 6% cocoa peel extract and 2% CHX. This research was conducted using the inhibition zone diffusion method against S. mutans to see the antibacterial power of each sample. Results: There was a significant difference (p <0.05) in the mean diameter of the inhibition zone between 6% cacao peel extract, namely 11.5406 mm and CHX 2%, namely 13.2156 mm.  Conclusion: Chlorhexidine digluconate 2% has a greater antibacterial power than 6% cocoa peel extract (Theobroma cacao L.) against Streptococcus mutans.